The Expression of TALEN before Fertilization Provides a Rapid Knock-Out Phenotype in Xenopus laevis Founder Embryos. - Kei Miyamoto; Ken-Ichi T Suzuki; Miyuki Suzuki; Yuto Sakane; Tetsushi Sakuma; Sarah Herberg; Angela Simeone; David Simpson; Jerome Jullien; Takashi Yamamoto; J B Gurdon (PLoS ONE)
Recent advances in genome editing using programmable nucleases have revolutionized gene targeting in various organisms. Successful gene knock-out has been shown in Xenopus, a widely used model organism, although a system enabling less mosaic knock-out in founder embryos (F0) needs to be explored in order to judge phenotypes in the F0 generation. Here, we injected modified highly active transcription activator-like effector nuclease (TALEN) mRNA to oocytes at the germinal vesicle (GV) stage, followed by in vitro maturation and intracytoplasmic sperm injection, to achieve a full knock-out in F0 embryos. Unlike conventional injection methods to fertilized embryos, the injection of TALEN mRNA into GV oocytes allows expression of nucleases before fertilization, enabling them to work from an earlier stage. Using this procedure, most of developed embryos showed full knock-out phenotypes of the pigmentation gene tyrosinase and/or embryonic lethal gene pax6 in the founder generation. In addition, our method permitted a large 1 kb deletion. Thus, we describe nearly complete gene knock-out phenotypes in Xenopus laevis F0 embryos. The presented method will help to accelerate the production of knock-out frogs since we can bypass an extra generation of about 1 year in Xenopus laevis. Meantime, our method provides a unique opportunity to rapidly test the developmental effects of disrupting those genes that do not permit growth to an adult able to reproduce. In addition, the protocol shown here is considerably less invasive than the previously used host transfer since our protocol does not require surgery. The experimental scheme presented is potentially applicable to other organisms such as mammals and fish to resolve common issues of mosaicism in founders.